2022
DOI: 10.31234/osf.io/c2naf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whose Signals Are Being Amplified? Towards a More Equitable Clinical Psychophysiology

Abstract: Research using psychophysiological methods holds great promise for refining clinical assessment, identifying risk factors, and informing treatment. Unfortunately, unique methodological features of existing approaches limit inclusive research participation and, consequently, generalizability. This brief overview and commentary provides a snapshot of the current state of representation in clinical psychophysiology, with a focus on the forms and consequences of ongoing exclusion of Black participants. We illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Phenotypic biases against dark skin tone and curly hair are present in optical imaging, which requires adequate contact with the scalp and is influenced by melanin 44 . As a result, participants with darker skin pigmentation and coarser hair (for instance, a large subset of the Black and Hispanic/Latino populations) are often excluded from EEG and fNIRS studies 40,45 . Excitingly, Etienne and colleagues have recently designed methods for obtaining high-quality EEG readings from individuals with coarse and curly hair, to address this systemic collection bias in EEG studies 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic biases against dark skin tone and curly hair are present in optical imaging, which requires adequate contact with the scalp and is influenced by melanin 44 . As a result, participants with darker skin pigmentation and coarser hair (for instance, a large subset of the Black and Hispanic/Latino populations) are often excluded from EEG and fNIRS studies 40,45 . Excitingly, Etienne and colleagues have recently designed methods for obtaining high-quality EEG readings from individuals with coarse and curly hair, to address this systemic collection bias in EEG studies 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Review the extant literature for recommendations by BIPOC researchers to increase inclusion of research participants and cite such researchers (Cundiff, 2012;Roberts et al, 2020;Zurn et al, 2020;Buchanan et al, 2021;Smith et al, 2021;Bradford et al, 2022;Webb et al, 2022).…”
Section: Specific Recommendations Across Methodsmentioning
confidence: 99%
“…Indeed, recent papers have highlighted the shortcomings of current neuroscience methods (Choy et al, 2021 ; Parker and Ricard, 2022 ; Webb et al, 2022 ). Recently, Bradford et al ( 2022 ) discussed underrepresentation in psychophysiological research samples and offered insightful recommendations for researchers to improve inclusion. We amplify and extend these valuable efforts, with a particular focus on methods that require access to participants' hair, such as electroencephalography (EEG) and hair sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…Even with spring-loaded grommets and tension tops on fNIRS caps, anecdotally, the signal quality for participants with coarse and/or curly hair is poor. As a result, individuals with coarse, curly, and dark hair -often people of African, African-American, and Caribbean descent -are excluded from fNIRS studies (14)(15)(16). Therefore, fNIRS datasets tend to underrepresent Black and Brown individuals, which supports the need for our review.…”
Section: Hair Typementioning
confidence: 95%
“…Additionally, NIR light can be attenuated by melanin, which is accounted for in neither fNIRS hardware nor analysis methods. Recent work has shown that overlooking these considerations in other modalities like EEG leads to the disproportionate exclusion of individuals with these phenotypes -especially Black people -in both clinical and research literature (Bradford et al 2022, Choy 2020. In this article, we sought to determine if (1) biomedical optics developers and researchers report fNIRS performance variability between skin tones and hair textures, (2a) fNIRS neuroscience practitioners report phenotypic and demographic details in their articles, and thus, (2b) is a similar pattern of participant exclusion found in EEG also present in the fNIRS literature.…”
mentioning
confidence: 99%